Numerical simulation of thermal radiation transmission in casson fluid flow with surface heat and mass fluxes - Hussain, Syed M.; Ahmad, Hijaz; Karim, Maimoona; Fadhl, Bandar M.; Jamshed, Wasim; Mohamed Isa, Siti Suzilliana Putri; Qureshi, Muhammad Amer; Khan, Abbas (Elsevier, 2025)
This study explores the heat and mass transfer behavior of Casson fluid flow induced by an exponentially stretching permeable surface embedded in a porous medium. The analysis incorporates variable surface heat and mass fluxes under the influence of thermal radiation transmission, a phenomenon relevant to numerous industrial and energy systems. The governing nonlinear partial differential equations are reduced to a set of similarity-based ordinary differential equations and solved numerically using the MATLAB bvp4c scheme. The results show that increasing the Casson parameter (β) suppresses the velocity, temperature, and concentration profiles, while wall suction markedly enhances both heat and mass transfer rates. A higher exponential stretching rate is observed to reduce the skin-friction coefficient and wall temperature gradient by nearly 9–12%. Quantitative comparisons confirm the reliability and accuracy of the proposed numerical approach. The study concludes that controlling suction and stretching parameters can effectively regulate thermal performance in radiative Casson fluid systems. The novelty of this work lies in the integrated consideration of radiation transmission with variable surface heat and mass fluxes in an exponentially stretched Casson flow , which has not been comprehensively addressed in the prior literature.